SAMPAIO, Fernando G. Bento Gonçalves: mito e história (sobre o herói ladrão farroupilha). - Sander, Wilson (Estudos Ibero-Americanos, 1984)
Porto Alegre, Martins Livreiro Ed., 1984. 141 p. 21 x 14,5cm.